Influence of Sex-Based Differences in Cardiac Phenotype on Atrial Fibrillation Recurrence in Patients Undergoing Pulmonary Vein Isolation - Yakimenka, Alena; Labib, Dina; Dykstra, Steven; Mikami, Yoko; Satriano, Alessandro; Flewitt, Jacqueline; Feuchter, Patricia; Rivest, Sandra; Howarth, Andrew G.; Lydell, Carmen P.; Quinn, F. Russell; Wilton, Stephen B.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Pulmonary vein isolation (PVI) is a commonly engaged therapy for symptomatic AF. Prior studies have documented elevated AF recurrence rates among females versus males. Sex-specific mechanisms underlying this phenomenon are poorly understood. This prospective cohort study aimed to evaluate the sex-based differences in cardiac phenotype and their influence on atrial fibrillation (AF) recurrence following first-time PVI. Methods: 204 consecutive patients referred for first-time PVI and 101 healthy subjects were prospectively studied by cardiovascular magnetic resonance imaging. Multi-chamber volumetric and functional measures were assessed by sex-corrected Z-score analyses versus healthy subjects. Patients were followed for a median of 2.6 years for the primary outcome of clinical AF recurrence. Multivariable analyses adjusting for age and comorbidities were performed to identify independent predictors of AF recurrence. Results: AF recurrence following the first PVI occurred in 41% of males and 59% of females (p=0.03). Females were older with a higher prevalence of hypertension and thyroid disorders. Z-score-based analyses revealed significantly reduced ventricular volumes, greater left atrial (LA) volumes and reduced LA contractility in females versus males. Multivariable analysis revealed each of LA minimum and pre-systolic volumes and booster EF Z-scores to be independently associated with AF recurrence, providing respective hazard ratios of 1.10, 1.19, and 0.89 (p=0.001, 0.03, and 0.01). Conclusion: Among patients referred for first-time PVI, females were older and demonstrated significantly poorer LA contractile health versus males, the latter independently associated with AF recurrence. Assessment of LA contractile health may therefore be of value to identify female patients at elevated risk of AF recurrence. Factors influencing female patient referral for PVI at more advanced stages of atrial disease warrant focused investigation.